2023
DOI: 10.3390/healthcare11020236
|View full text |Cite
|
Sign up to set email alerts
|

Couple-Based Communication Interventions for Cancer Patient–Spousal Caregiver Dyads’ Psychosocial Adaptation to Cancer: A Systematic Review

Abstract: (1) Background: Effective communication among couples in which one has been diagnosed with cancer is critical to improve their psychosocial adaptation to cancer. The objective of this review was to explore the characteristics and measurement outcomes of existing couple-based communication interventions in the cancer context. (2) Methods: Eight electronic databases were searched from database initiation to August 2022 to identify eligible articles. Hand searching was also performed on the included articles’ ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Among the reviews conducted, eight employed the Cochrane criteria to evaluate quality (Brandão et al, 2014;Guan et al, 2023;Hu et al, 2019;Li et al, 2023;McDonnell et al, 2022;Pang et al, 2022;Wang et al, 2021), and six adopted the Effective Public Health Practice Project Li et al, 2020;Li & Loke, 2014;Luo et al, 2020;Regan et al, 2012;Zhou et al, 2023). , 2018;Li et al, 2020;Pang et al, 2022;Song et al, 2021).…”
Section: Description Of the Included Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the reviews conducted, eight employed the Cochrane criteria to evaluate quality (Brandão et al, 2014;Guan et al, 2023;Hu et al, 2019;Li et al, 2023;McDonnell et al, 2022;Pang et al, 2022;Wang et al, 2021), and six adopted the Effective Public Health Practice Project Li et al, 2020;Li & Loke, 2014;Luo et al, 2020;Regan et al, 2012;Zhou et al, 2023). , 2018;Li et al, 2020;Pang et al, 2022;Song et al, 2021).…”
Section: Description Of the Included Reviewsmentioning
confidence: 99%
“…Sixteen reviews reported psychological outcomes (e.g. psychological distress, anxiety, depression), while 11 documented relationship functioning and quality of life (Badr & Krebs, 2013;Brandão et al, 2014;Chen, Gong, & Li, 2022;Hu et al, 2019;Jonsdottir et al, 2018;Li et al, 2023;Li & Loke, 2014;Luo et al, 2020;Regan et al, 2012;Song et al, 2021;Zhou et al, 2023).…”
Section: Description Of the Included Reviewsmentioning
confidence: 99%
See 3 more Smart Citations